2010
DOI: 10.1055/s-0039-1697866
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of the Relationship between the Maxillary Sinus Floor and the Maxillary Posterior Teeth Root Tips Using Dental Cone-beam Computerized Tomography

Abstract: Objectives:The aim of the present study was to assess the relationship between the maxillary sinus floor and the maxillary posterior teeth root tips using dental cone-beam CT.Methods:A total of 87 right and 89 left maxillary sinus regions from 92 patients were examined using dental cone-beam CT. Images were analyzed by a specialist in oral and maxillofacial radiology. Perpendicular lines were drawn on the cross-sectional images between the deepest point of the maxillary sinus floor and the root tips of the max… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

26
128
5
17

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(176 citation statements)
references
References 21 publications
26
128
5
17
Order By: Relevance
“…The most frequent relationship in previous studies was that the sinus floor did not contact the roots of the molars 1,8,9. Meanwhile, apical protrusion into the maxillary sinus (Type 3) of one or more roots of the molars was most frequent in our study although the roots being separate from the sinus (Type 0) was most frequent in each root of the molars.…”
Section: Discussioncontrasting
confidence: 45%
See 2 more Smart Citations
“…The most frequent relationship in previous studies was that the sinus floor did not contact the roots of the molars 1,8,9. Meanwhile, apical protrusion into the maxillary sinus (Type 3) of one or more roots of the molars was most frequent in our study although the roots being separate from the sinus (Type 0) was most frequent in each root of the molars.…”
Section: Discussioncontrasting
confidence: 45%
“…Most studies have revealed that the buccal roots of M2 are closely related to the floor of the maxillary sinus 1,8,10-12. Eberhardt et al8 and Georgescu et al12 reported that the mesiobuccal roots of M2 were closest to the sinus floor, and Kilic et al1 reported that the distobuccal root of M2 was closest to the sinus floor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Contradictory, no significant difference of thickness of Schneiderian membrane between genders was also reported by other authors. 23,25 In this study, the most frequently detected membrane abnormality was flat-type thickening (21% of the CBCT scans 26,27 Similar to the previous study, mesiobuccal root apexes of the second molar were frequently penetrating the sinus floor. 26 It should be mentioned that an association between the prevalence of maxillary sinus mucosal thickening and the anatomical relationship between the sinus floor and posterior teeth root apexes was previously reported.…”
Section: Discussionsupporting
confidence: 83%
“…However, another different classification was done by Kilic et al 2010 35 who classified the targeted relationship on CBCT images to only three types 1, 2& 3 with type 1 representing roots penetrating MSF, type 2 representing roots contacting MSF and type 3 representing roots not reaching MSF, then this classification was used again by Ok et al 2014 36 on CBCT images of Turkish population. Later on, in 2016 Tian et al 37 .…”
Section: Discussionmentioning
confidence: 99%